A CONTRIBUTION TO RESEARCH OF THE INFLUENCE OF STEERING TRAPEZE ON BUS STEERED WHEELS SHIMMY - Demić, Miroslav; Diligenski, Đorđe (Journal of Applied Engineering Science, 2013)
Steered wheels shimmy is a harmful phenomenon in the steering system of the vehicle. It causes driver’s fatigue and fatigue of the elements of steering system, increased tire wear etc. In practice, efforts are being made to reduce or eliminate the occurrence of this effect, and the buses are sometimes equipped with shock absorbers in the steering trapeze. In this paper an attempt is made to analyze the influence of shock absorber in the steering trapeze on the steered wheels shimmy of a bus. Analysis showed that shock absorbers significantly affect the reduction of steered wheels shimmy.
Keywords: Steered wheels shimmy; Shock absorber; Bus